Sources and microbiological quality of domestic water in three rural communities in the southern Caribbean - Akilah Stewart; Catherine Seepersad; Aliya Hosein; John Agard; Adrian Cashman; Dave Chadee; Adesh Ramsubhag (IWA Publishing, 2023)
This study investigated the sources and microbiological quality of domestic water used by rural communities of Speightstown, Barbados; Carriacou, Grenada; and Nariva, Trinidad. The primary water source was harvested rainwater in Carriacou, and the public water supply for Nariva and Speightstown. Secondary water supplies of the communities came from untreated sources including rainwater, wells, boreholes and springs. E. coli was detected at higher frequencies in water from Carriacou (41.3%) and Nariva (47.4%) than Speightstown (3.6%). Generally, more untreated samples of rainwater (44.6%) and surface/ground water (58.3%) were E. coli positive than treated water obtained from the public supply (9.9%). These findings demonstrate the increased risk to residents in rural communities of the Caribbean who utilize untreated rainwater and environmental sources such as springs and wells. These results demonstrate the usefulness of traditional methods such as the compartment bag test in determining the microbiological quality of domestic water in resource-challenged rural communities of the Caribbean. HIGHLIGHTS Residents from Carriacou depended on harvested rainwater while those in Speightstown and Nariva relied more on the public distribution system.; E. coli was detected at higher frequencies in water samples from Carriacou and Nariva than Speightstown.; More untreated samples of rainwater and surface/ground water were E. coli positive.; The CBT method proved useful for determining microbiological water quality in rural communities.;